Application effect of three-dimensional CT measurement-assisted design in one-stage total auricular reconstruction - KUANG Jianguo, LIU Qiang, PAN Xinting, ZHU Qingyun (精准医学杂志)
Objective To investigate the clinical effect of one-stage total auricular reconstruction based on the three-dimensional CT measurement-assisted design. Methods A total of 49 patients who underwent one-stage total auricular reconstruction based on the three-dimensional CT measurement-assisted design of the superficial temporal fascia flap in our hospital were enrolled in this study. Whether the harvested tissue flaps needed to be trimmed was observed during surgery, as well as the immediate morphology of the reconstructed auricle, and the patients were followed up after surgery to observe the survival of the fascia tissue flap, the morphology of the reconstructed auricle, and its symmetry with the contralateral side. Results The tissue flaps of all patients collected during surgery did not need to be trimmed, and the tissue flap covered the ear scaffold very well, resulting in a good immediate morphology of the auricle. After surgery, the tissue flaps covering the ear scaffold all survived in the first stage, and the size of the reconstructed auricle and the cranioauricular angle were basically consistent with the contralateral side. The structures of the helix, antitragus, triangular fossa, concha, and earlobe became clearer over time. Conclusion The three-dimensional CT measurement-assisted design before one-stage total auricular reconstruction helps to precisely collect the tissue flap used to cover the ear scaffold, with a satisfactory clinical effect and a favorable safety profile after surgery. Therefore, it holds promise for clinical application.